The coexistence of ferroelectricity and topological phase transition in monolayer α-In2Se3 under strain engineering. (4th December 2019) - Jiang, Xingxing; Feng, Yexin; Chen, Ke-Qiu; Tang, Li-Ming
Abstract: The coexistence of ferroelectricity and topological phase transition in monolayer α -In2 Se3 through strain engineering are investigated by first-principles calculation. The results show that with the spontaneous polarization increasing, the transition barrier decreases, approximately linearly related to the applied strain, and the effect of biaxial compressive strain within the in-plane is two orders of magnitude greater than that of tensile strain along the out-of-plane. The results also show that a Dirac cone with a linear dispersion relationship occurs at the high symmetry Γ point within the Brillouin region whatever strain pattern is applied. By analyzing the orbital characters of the electronic states near the Fermi level we find that the electronic structure presents obvious topological phase transition, indicating that monolayer α -In2 Se3 is not only an excellent 2D ferroelectric material but also a topological material.